Efektivitas E-Government di Mall Pelayanan Publik Kabupaten Pandeglang - Parko Prahima; Dede Qodrat Al-Wajir; Arief Rachman; Sri Atomy; Zepanya Manurung (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2023)
The low quality of public services is still a classic problem in Indonesia. Therefore, it is time for the government to implement e-government as an effort to improve services to the community. This research aims to determine the effectiveness of making online SKCK at MPP Pandeglang Regency as an implementation of e-government and to determine the factors that support and hinder e-government at MPP Pandeglang Regency. The research uses a qualitative method with a descriptive approach, a case study of making online SKCK at the Pandeglang Regency MPP. This research found that the effectiveness of e-government as seen from the indicators of productivity, adaptability, job satisfaction and general development is good. The supporting factor is the availability of adequate facilities and infrastructure. Meanwhile, the inhibiting factors are the lack of human resources and inappropriate placement of officers. This research has the implication that the e-government services provided should be socialized first so that they can be implemented optimally in society.